2010
DOI: 10.1080/02640410903502782
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-motor delay, information–movement coupling, and expertise in ball sports

Abstract: We compared the performance of tennis experts and non-experts using a simulated interceptive task, in which the ball could be unexpectedly deviated 400 ms before contact. The results showed that experts were more accurate than non-experts when intercepting balls that deviated in their trajectory and that this could be explained by their shorter visuo-motor delay in adapting their interceptive movement. In addition, multiple regression analyses revealed that visuo-motor delay was a good predictor of accuracy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
35
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 25 publications
5
35
0
4
Order By: Relevance
“…However, the features that distinguish expertise in fast ball sports are a better adaptation of the perceptual motor system to unexpected environmental changes under time constraints (Runigo et al 2010). This may be the result of shorter visuomotor delay and efficient reprogramming of motor responses within limited time periods (Nakamoto and Mori 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, the features that distinguish expertise in fast ball sports are a better adaptation of the perceptual motor system to unexpected environmental changes under time constraints (Runigo et al 2010). This may be the result of shorter visuomotor delay and efficient reprogramming of motor responses within limited time periods (Nakamoto and Mori 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Runigo and colleagues (2005) found that VMD is shorter in expert tennis players (162 ms) compared with novices (221 ms) (see also McLeod, 1987). It was concluded that this shorter VMD offers more time to adapt the interceptive movement to the changed environment and thereby improves the accuracy of the outcome (Runigo, Benguigui, & Bardy, 2010;Runigo et al, 2005). However, Teixeira and colleagues (2005) pointed out that even when the sign of movement adjustment is observed, it is not necessarily the case that adequate movement correction occurs in ordinary adults (see also Teixeira et al, 2006a).…”
Section: Introductionmentioning
confidence: 95%
“…One of these issues is study of features of sensomotor integration in functional systems of motor activity in women boxers. Sensomotor integration effectiveness allows formation of potent adaptive strategies in competitive fighting [Wolpert et al, 1995;Del Parcio et al, 2009;Le Runigo et al, 2010]. …”
mentioning
confidence: 99%